Histological and Clinical Findings in Patients with Post-Transplantation and Classical Encapsulating Peritoneal Sclerosis: A European Multicenter Study - Latus, Joerg (Public Library of Science, 2014)
BACKGROUND: Encapsulating peritoneal sclerosis (EPS) commonly presents after peritoneal dialysis has been stopped, either post-transplantation (PT-EPS) or after switching to hemodialysis (classical EPS, cEPS). The aim of the present study was to investigate whether PT-EPS and cEPS differ in morphology and clinical course. METHODS: In this European multicenter study we included fifty-six EPS patients, retrospectively paired-matched for peritoneal dialysis (PD) duration. Twenty-eight patients developed EPS after renal transplantation, whereas the other twenty-eight patients were classical EPS patients. Demographic data, PD details, and course of disease were documented. Peritoneal biopsies of all patients were investigated using histological criteria. RESULTS: Eighteen patients from the Netherlands and thirty-eight patients from Germany were included. Time on PD was 78(64–95) in the PT-EPS and 72(50–89) months in the cEPS group (p>0.05). There were no significant differences between the morphological findings of cEPS and PT-EPS. Podoplanin positive cells were a prominent feature in both groups, but with a similar distribution of the podoplanin patterns. Time between cessation of PD to the clinical diagnosis of EPS was significantly shorter in the PT-EPS group as compared to cEPS (4(2–9) months versus 23(7–24) months, p<0.001). Peritonitis rate was significantly higher in cEPS. CONCLUSIONS: In peritoneal biopsies PT-EPS and cEPS are not distinguishable by histomorphology and immunohistochemistry, which argues against different entities. The critical phase for PT-EPS is during the first year after transplantation and therefore earlier after PD cessation then in cEPS.